Culture and imperialism - Said, Edward W. (London Chatto & Windus Ltd, 1993)
A landmark work from the intellectually auspicious author of Orientalism that explores the long-overlooked connections between the Western imperial endeavor and the culture that both reflected and reinforced it.
Part 1. Chapters 1 and 2 -- part 2. Chapters 3 and 4.
Photocopy.
Includes bibliographical references (pages 409-432) and index.
Keywords: European literature -- History and criticism -- Theory, etc; Literature -- History and criticism -- Theory, etc; Imperialism in literature; Colonies in literature; Politics and culture